2012
DOI: 10.1002/anie.201106584
|View full text |Cite
|
Sign up to set email alerts
|

Thiolate‐Induced Metal Adatom Trapping at Solid–Liquid Interfaces

Abstract: Organosulfur compounds, in particular thiolates, are one of the most important classes of surface-active species and have very diverse applications. On the one hand, they are extensively employed in molecular self-assembly, for which they may be considered as the archetypal system, with wide ranging applications in nanoscience (for example molecular electronics, immobilization of biomolecules, and stabilization of nanoparticles). [1][2][3] On the other hand, organosulfur species have been empirically developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 16 publications
4
28
0
Order By: Relevance
“…This is similar to our previous data for CH 3 S ad adsorbed on the Cu(1 0 0) surface, where repulsive CH 3 S ad -CH 3 S ad interactions of 22 to 33 meV were measured [18,19]. The arrangement in alternating CH 3 S sp -Cu chains suggests effective attractive interactions, but in view of the complex interface structure with different species in the metal surface and the adsorbate plane the origin of these interactions is difficult to access.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This is similar to our previous data for CH 3 S ad adsorbed on the Cu(1 0 0) surface, where repulsive CH 3 S ad -CH 3 S ad interactions of 22 to 33 meV were measured [18,19]. The arrangement in alternating CH 3 S sp -Cu chains suggests effective attractive interactions, but in view of the complex interface structure with different species in the metal surface and the adsorbate plane the origin of these interactions is difficult to access.…”
Section: Discussionsupporting
confidence: 89%
“…At more positive potentials the STM studies revealed a coexistence of those adlayers with the (kinetically slowly formed) Cu reconstruction. This potential dependent phase behavior is very different from that observed in our extensive Video-STM studies of adsorbed methyl thiolate on Cu(1 0 0) in the potential range À0.40 to À0.20 V. Here, no indication for surface reconstruction was found, but the Cu surface was covered by a mixed CH 3 S ad /Cl ad adlayer with c(2 Â 2) structure or, at higher CH 3-S ad coverages, a coexistence of this c(2 Â 2) phase with islands of a c(6 Â 2) CH 3 S ad adlayer [18,19]. Formation of the Cu reconstruction exclusively occurred at potentials of À0.6 V or lower, with the speed of the reconstruction process strongly increasing towards more negative potentials.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations